EBO technical review of the validity of Recommendation #14 of the Clinical Practice Guidelines for the Management of Cataract among Adults - Jacqueline Hernandez-King, MD (Philippine Journal of Ophthalmology)
Purpose: To assess the current validity of Recommendation #14, which states that both phacoemulsification and extracapsular cataract extraction (ECCE) are acceptable techniques among patients undergoing cataract surgery.